Integrating Contextual Learning and Digital Media to Boost English Language Skills - Maulya, Ranti; Sari, Desi Purnama; Sarinauli, Barep; Kamarullah, Kamarullah; Sabariah, Sabariah (Universitas Muhammadiyah Jember, 2025)
This study examines the impact of utilizing local tourist sites as a contextual medium to enhance English language learning through student-created promotional videos produced in a vlogger style. Conducted with 34 senior high school students from MAN 1 Aceh Tengah, Indonesia, this research employs a mixed-methods approach, combining quantitative data from pre- and post-test English proficiency scores and qualitative insights from student and teacher interviews. The quantitative data analysis involved paired sample t-tests, revealing a significant improvement in students' English proficiency, with post-test scores showing an average increase of 11.5 points compared to pre-test scores (p < 0.001). The qualitative thematic analysis highlighted several critical outcomes: students experienced greater motivation, enjoyment, and increased self-confidence in using English due to authentic interactions during visits to tourist sites. Additionally, the project fostered essential 21st-century skills such as collaboration, creativity, and digital literacy, enhancing overall student engagement and language acquisition. Teachers also expressed positive perceptions, noting the method's effectiveness in connecting theoretical learning to real-world contexts. The findings indicate that using local contexts and student-led digital projects can bridge classroom learning and real-world language use, offering practical insights for educators seeking innovative ways to enhance English proficiency in Indonesian-like settings.